Synthesis and Evaluation of Thiol-Conjugated Poloxamer and Its Pharmaceutical Applications - Muhammad Zaman; Sadaf Saeed; Rabia Imtiaz Bajwa; Muhammad Shafeeq Ur Rahman; Saeed Ur Rahman; Muhammad Jamshaid; Muhammad F. Rasool; Abdul Majeed; Imran Imran; Faleh Alqahtani; Sultan Alshehri; Abdullah F. AlAsmari; et al. (Pharmaceutics, 2021)
The current study was designed to convert the poloxamer (PLX) into thiolated poloxamer (TPLX), followed by its physicochemical, biocompatibilities studies, and applications as a pharmaceutical excipient in the development of tacrolimus (TCM)-containing compressed tablets. Thiolation was accomplished by using thiourea as a thiol donor and hydrochloric acid (HCl) as a catalyst in the reaction. Both PLX and TPLX were evaluated for surface morphology based on SEM, the crystalline or amorphous nature of the particles, thiol contents, micromeritics, FTIR, and biocompatibility studies in albino rats. Furthermore, the polymers were used in the development of compressed tablets. Later, they were also characterized for thickness, diameter, hardness, weight variation, swelling index, disintegration time, mucoadhesion, and in vitro drug release. The outcomes of the study showed that the thiolation process was accomplished successfully, which was confirmed by FTIR, where a characteristic peak was noticed at 2695.9968 cm−1 in the FTIR scan of TPLX. Furthermore, the considerable concentration of the thiol constituents (20.625 µg/g of the polymer), which was present on the polymeric backbone, also strengthened the claim of successful thiolation. A mucoadhesion test illustrated the comparatively better mucoadhesion strength of TPLX compared to PLX. The in vitro drug release study exhibited that the TPLX-based formulation showed a more rapid (p < 0.05) release of the drug in 1 h compared to the PLX-based formulation. The in vivo toxicity studies confirmed that both PLX and TPLX were safe when they were administered to the albino rats. Conclusively, the thiolation of PLX made not only the polymer more mucoadhesive but also capable of improving the dissolution profile of TCM.